2018
DOI: 10.1177/0004867418806370
|View full text |Cite
|
Sign up to set email alerts
|

The right thalamic glutamate level correlates with functional connectivity with right dorsal anterior cingulate cortex/middle occipital gyrus in unmedicated obsessive–compulsive disorder: A combined fMRI and 1H-MRS study

Abstract: Objective: The imbalance in neurotransmitter and neuronal metabolite concentration within cortico-striato-thalamocortical (CSTC) circuit contributes to obsessive-compulsive disorder's (OCD) onset. Previous studies showed that glutamate mediated upregulation of resting-state activity in healthy people. However, there have been few studies investigating the correlational features between functional and neurochemical alterations in OCD. Methods: We utilize a combined resting-state functional magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Interestingly, our results were more in line with previous connectivity studies using resting‐state functional imaging in patients with OCD. For example, functional connectivity alterations in OCD have been found between the caudate and temporo‐occipital regions 60‐62 and between the thalamus and occipital cortex 63‐65 . Speculatively, our findings of reduced structural connectivity between occipital and subcortical structures might be associated with visuospatial deficits, which are observed in patients with OCD 66‐70 .…”
Section: Discussionmentioning
confidence: 52%
“…Interestingly, our results were more in line with previous connectivity studies using resting‐state functional imaging in patients with OCD. For example, functional connectivity alterations in OCD have been found between the caudate and temporo‐occipital regions 60‐62 and between the thalamus and occipital cortex 63‐65 . Speculatively, our findings of reduced structural connectivity between occipital and subcortical structures might be associated with visuospatial deficits, which are observed in patients with OCD 66‐70 .…”
Section: Discussionmentioning
confidence: 52%
“…Obsessive-compulsive disorder (OCD) is defined as a combination of intrusive thoughts (obsessions) and repetitive behaviors (compulsions), which affects social and occupational functions and imposes an economic burden on patients and their families [1,2]. Although the pathophysiological mechanism of OCD remains unclear, neuroimaging studies have highlighted abnormalities in the cortical-striatal-thalamic-cortical (CSTC) circuit, including the anterior cingulate cortex, orbitofrontal cortex (OFC), dorsolateral prefrontal cortex (DLPFC), thalamus, and striatum [3][4][5][6]. For example, increased and decreased levels of gray matter volumes in the left OFC and striatum and increased regional homogeneity (ReHo) and global brain functional connectivity (FC) in the lateral OFC and DLPFC were discovered at rest in OCD [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence from basic neurobiological studies have indicated the role of glutamatergic abnormalities in the pathogenesis of OCD. [16][17][18]29,30 These studies demonstrated pathologically elevated glutamatergic transmission in the cortical-striatal-thalamic circuitry of the brain in the OCD patients. Following treatment, the decrease in caudate glutamatergic concentration is associated with the decrease in OCD severity.…”
Section: Discussionmentioning
confidence: 79%
“…First, research has revealed pathologically elevated glutamatergic transmission in cortical-striatal-thalamic circuit of the brain in OCD patients. 16,17 Following treatment with glutamate modulating agents, a decrease in OCD symptoms severity was detected. [18][19][20][21] Further evidence for glutamatergic dysfunction in OCD comes from studies that measured levels of glutamate in cerebrospinal fluid (CSF) of OCD patients and matched psychiatrically normal controls.…”
Section: Introductionmentioning
confidence: 99%